Surface science : foundations of catalysis and nanoscience - Kolasinski, Kurt W. (Wiley, 2012)
Front Matter -- Introduction -- Surface and Adsorbate Structure -- Experimental Probes and Techniques -- Chemisorption, Physisorption and Dynamics -- Thermodynamics and Kinetics of Adsorption and Desorption -- Liquid Interfaces -- Heterogeneous Catalysis -- Growth and Epitaxy -- Laser and Non-Thermal Chemistry: Photon and Electron Stimulated Chemistry and Atom Manipulation -- Answers to Exercises from Chapter 1. Surface and Adsorbate Structure -- Answers to Exercises from Chapter 2. Experimental Probes and Techniques -- Answers to Exercises from Chapter 3. Chemisorption, Physisorption and Dynamics -- Answers to Exercises from Chapter 4. Thermodynamics and Kinetics of Adsorption and Desorption -- Answers to Exercises from Chapter 5. Liquid Interfaces -- Answers to Exercises from Chapter 6. Heterogeneous Catalysis -- Answers to Exercises From Chapter 7. Growth and Epitaxy -- Answers to exercises from Chapter 8. Laser and Nonthermal Chemistry -- Appendix I: Abbreviations and Prefixes -- Appendix II: Symbols -- Appendix III: Useful Mathematical Expressions -- logarithmic table -- Index.